Implementation of Power Factor Correction using Asynchronous Boost Converter on Single Phase Full-Bridge Diode - Saputra, Masramdhani; Ridzki, Imron; Wiwaha, Sigit Setya; Djulihenanto, Saddani (Faculty of Engineering, Universitas Brawijaya, 2023)
In various industrial applications, the use of a power supply that uses a conventional diode single-phase rectifier topology results in high harmonic values in the electricity distribution system. One of the real impacts of this harmonic value is the heating of the electric power system equipment and power losses. High rms current values due to harmonics often cause problems in protection settings in addition to efficiency problems. The percentage value between the total harmonic component and the fundamental component is called THD (Total Harmonic Distortions). Therefore, in this study an asynchronous dcdc boost converter is connected to the output side of a singlephase diode rectifier which is capable of improving power factor and low harmonics. So that a THD value of less than 15%, PF (Power Factor) = 0.92-1 and a sinusoidal input current can be obtained. The implementation results show that the PFC (Power Factor Correction) method can work well on single-phase diode rectifiers.